2008
DOI: 10.1002/rem.20171
|View full text |Cite
|
Sign up to set email alerts
|

Lead in soil by field‐portable x‐ray fluorescence spectrometry—an examination of paired In Situ and laboratory ICP‐AES results

Abstract: A major aspect of lead hazard control is the evaluation of soil lead hazards around housing coated with lead-based paint. The use of field-portable X-ray fluorescence (FPXRF) to do detailed surveying, with limited laboratory confirmation, can provide lead measurements in soil (especially for planning abatement activities) in a far more cost-efficient and timely manner than laboratory analysis. To date, one obstacle to the acceptance of FPXRF as an approved method of measuring lead in soil has been a lack of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…However, paint chips in the dust wipe samples can confound the results (Sterling et al, 2000). When comparing FP-XRF analysis and ICP-AES analysis for bulk samples of soil around homes with lead-based paint Binstock et al (2009) found no statistical difference between the two methods in soil with particle sizes less than 250 µm. When comparing ICP and XRF for lead on surface wipes, Harper et al (2002) concluded that the XRF underestimated the concentrations but still found strong liner relationships between the two methods.…”
Section: Introductionmentioning
confidence: 97%
“…However, paint chips in the dust wipe samples can confound the results (Sterling et al, 2000). When comparing FP-XRF analysis and ICP-AES analysis for bulk samples of soil around homes with lead-based paint Binstock et al (2009) found no statistical difference between the two methods in soil with particle sizes less than 250 µm. When comparing ICP and XRF for lead on surface wipes, Harper et al (2002) concluded that the XRF underestimated the concentrations but still found strong liner relationships between the two methods.…”
Section: Introductionmentioning
confidence: 97%
“…In many communities, lead (Pb) contamination remains the primary culprit. This heavy metal, which is an artifact of anthropogenic activity, has entered the soil primarily as a result of the prolonged use of leaded gasoline in the internal combustion engine and leaded paint applied inside and outside of many buildings from approximately the 1920s until 1996 and 1978 in the United States, respectively (Binstock et al., 2008; Markey et al, 2008; McBride et al., 2011; Schwarz et al., 2012). Human exposure has been linked to a variety of health maladies, leading the U.S. Centers for Disease Control and Prevention to recommend action at blood Pb levels exceeding 5 μg dl −1 (CDC, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, several physico-chemical parameters of soil are known to affect the quality and the precision of PXRF reading, essentially sample matrix, surface irregularity, interfering elements, mineralogy, particle size and soil moisture [9,[11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%